Book Reviews. Issue 1 (1st March 2022) - Unknown
Abstract : Owen White, The Blood of the Colony: Wine and the Rise and Fall of French Algeria (Cambridge, MA: Harvard University Press, 2020). Andrea E. Duffy, Nomad's Land: Pastoralism and French Environmental Policy in the Nineteenth-Century Mediterranean World (Lincoln: University of Nebraska Press, 2019). Charlotte Ann Legg, The New White Race: Settler Colonialism and the Press in French Algeria, 1860–1914 (Lincoln: University of Nebraska Press, 2021).